2020
DOI: 10.3390/en13195033
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to the Analysis of Thermal Response Test (TRT) with Interrupted Power Input

Abstract: The quality of measuring datasets of the thermal response test (TRT) significantly influences the interpretation of borehole thermal parameters (BTP). A thermal response test with an unstable power input may induce an unacceptable error in the estimation of the borehole thermal parameters. This paper proposes a novel approach to treat the dataset with interrupted power input. In this approach, the test records were segmented into several subsections with a constant time interval of 100 min, 60 min, and 30 min,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Mogensen [22] reported values λ g = 2.69 W/m K and R b = 0.1266 K/W m, while Reuss [19] reported that λ g = 2.2 W/m K and ρc = 2.8 MJ/m 3 K. Gehlin [20] indicated that the thermal conductivity of the ground when a borehole is filled with grout is 3.45 W/m K, while it is 3.62 W/m K when filled with water. In recent years, studies in [23][24][25][26][27][28][29][30][31] showed improvements and applications of the TRT procedure for evaluating BHE efficiency. Luo et al [23] studied the influence of an unstable power input on the unacceptable errors of the TRT measured data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mogensen [22] reported values λ g = 2.69 W/m K and R b = 0.1266 K/W m, while Reuss [19] reported that λ g = 2.2 W/m K and ρc = 2.8 MJ/m 3 K. Gehlin [20] indicated that the thermal conductivity of the ground when a borehole is filled with grout is 3.45 W/m K, while it is 3.62 W/m K when filled with water. In recent years, studies in [23][24][25][26][27][28][29][30][31] showed improvements and applications of the TRT procedure for evaluating BHE efficiency. Luo et al [23] studied the influence of an unstable power input on the unacceptable errors of the TRT measured data.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies in [23][24][25][26][27][28][29][30][31] showed improvements and applications of the TRT procedure for evaluating BHE efficiency. Luo et al [23] studied the influence of an unstable power input on the unacceptable errors of the TRT measured data. They reported two approaches, including continuous and semi-superposition algorithms, for efficient interpretation of datasets obtained with interrupted power inputs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation